Sampling best response dynamics and deterministic equilibrium selection - William H. Sandholm; Olivier Tercieux; Daisuke Oyama (Theoretical Economics, 2015)
We consider a model of evolution in games in which a revising agent observes the actions of a random number of randomly sampled opponents and then chooses a best response to the distribution of actions in the sample. We provide a condition on the distribution of sample sizes under which an iterated p-dominant equilibrium is almost globally asymptotically stable under these dynamics. We show under an additional condition on the sample size distribution that in supermodular games, an almost globally asymptotically stable state must be an iterated p-dominant equilibrium. Since our selection results are for deterministic dynamics, any selected equilibrium is reached quickly; the long waiting times associated with equilibrium selection in stochastic stability models are absent.
Keywords: C72; C73; 330; Evolutionary game dynamics; almost global convergence; iterated p-dominance; equilibrium selection